Reference range evaluation of complete blood count parameters with emphasis on newer research parameters on the complete blood count analyzer Sysmex XE-2100 - Kunal K Sehgal; Dadu Tina; Urmi Choksey; Reeta J Dalal; Khodaiji J Shanaz (Wolters Kluwer Medknow Publications, 2013)
Since the advent of automation in the field of hematological cell counters there has been a constant refinement of the technology and increase in the number of newer parameters available on CBC analysers. Many novel parameters are being put into routine clinical use and both clinical evaluation and monitoring critically depend on knowledge of laboratory reference ranges. Here, we present reference interval for the Sysmex XE-2100, with emphasis on the novel or newer research parameters. Blood samples from a total of 122 clinically asymptomatic and apparently healthy subjects were evaluated and a final of 100 subjects (54-M, 46-F) were included in the study. A broad spectrum of parameters available with the analyser was assessed and reference ranges for the same evaluated.